Helminth parasites of Xiphophorus birchmanni (Pisces: Poeciliidae) from two localities of the Pánuco River drainage, Mexico - Christian Elizbeth Bautista-Hernández; Griselda Pulido-Flores; Juan Violante-González; Scott Monks (Revista Mexicana de Biodiversidad)
Specimens of Xiphophorus birchmanni (Teleostei: Poeciliidae) (55 individuals) (Sheepshead swordtail) were collected from 2 localities in the Pánuco River drainage from Hidalgo and Veracruz [at Atlatipa (n = 26) and Benito Juárez (n = 29), respectively], Mexico. The structure of the parasite communities of fish from the 2 localities was examined and compared. Helminths from 10 taxa were recovered: 6 species of larval digeneans (Posthodiplostomum sp., Uvulifer sp., Centrocestus formosanus, Ascocotyle sp., Haplorchis pumilio, and Echinostomatidae gen. sp.); 2 adult monogeneans (Urocleidoides vaginoclastrum and Gyrodactylus sp.); 1 larval cestode (metacestode stage; Glossocercus auritus); and 1 larval nematode, Eustrongylides sp. Urocleidoides vaginoclastrum and C. formosanus were the most frequent and abundant species. The remaining taxa were rare and found at low mean abundance. Component community and infracommunity differences observed in this study could be attributed to abiotic and biotic environmental factors resulting from the geographic separation of these localities during the orogeny of the Sierra Madre Oriental that restricted fish to isolated localities.